Outcomes After TIPS for Ascites and Variceal Bleeding in a Contemporary Era—An ALTA Group Study. (23rd October 2021) - Boike, Justin Richard; Mazumder, Nikhilesh Ray; Kolli, Kanti Pallav; Ge, Jin; German, Margarita; Jest, Nathaniel; Morelli, Giuseppe; Spengler, Erin; Said, Adnan; Lai, Jennifer C.; Desai, Archita P.; Couri, Thomas; et al.
Abstract : INTRODUCTION: Advances in transjugular intrahepatic portosystemic shunt (TIPS) technology have led to expanded use. We sought to characterize contemporary outcomes of TIPS by common indications. METHODS: This was a multicenter, retrospective cohort study using data from the Advancing Liver Therapeutic Approaches study group among adults with cirrhosis who underwent TIPS for ascites/hepatic hydrothorax (ascites/HH) or variceal bleeding (2010–2015). Adjusted competing risk analysis was used to assess post-TIPS mortality or liver transplantation (LT). RESULTS: Among 1, 129 TIPS recipients, 58% received TIPS for ascites/HH and 42% for variceal bleeding. In patients who underwent TIPS for ascites/HH, the subdistribution hazard ratio (sHR) for death was similar across all Model for End-Stage Liver Disease Sodium (MELD-Na) categories with an increasing sHR with rising MELD-Na. In patients with TIPS for variceal bleeding, MELD-Na ≥20 was associated with increased hazard for death, whereas MELD-Na ≥22 was associated with LT. In a multivariate analysis, serum creatinine was most significantly associated with death (sHR 1.2 per mg/dL, 95% confidence interval [CI] 1.04–1.4 and 1.37, 95% CI 1.08–1.73 in ascites/HH and variceal bleeding, respectively). Bilirubin and international normalized ratio were most associated with LT in ascites/HH (sHR 1.23, 95% CI 1.15–1.3; sHR 2.99, 95% CI 1.76–5.1, respectively) compared with only bilirubin in variceal bleeding (sHR 1.06, 95% CI 1.00–1.13). DISCUSSION: MELD-Na has differing relationships with patient outcomes dependent on TIPS indication. These data provide new insights into contemporary predictors of outcomes after TIPS.